2019
DOI: 10.1186/s13049-019-0672-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients treated by the Danish Helicopter Emergency Medical Service from 2014-2018: a nationwide population-based study

Abstract: BackgroundA national Helicopter Emergency Medical Service (HEMS) was introduced in Denmark in 2014 to ensure the availability of physician-led critical care for all patients regardless of location.Appropriate dispatch of HEMS is known to be complex, and resource utilisation is a highly relevant topic. Population-based studies on patient characteristics are fundamental when evaluating and optimising a system. The aim of this study was to describe the patient population treated by the Danish HEMS in terms of dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 19 publications
(21 reference statements)
4
43
0
Order By: Relevance
“…This is supported by a recent study where we demonstrated that patients escorted by HEMS had an increased severity score and more often had a critical care intervention performed compared with the assisted patients. 3 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is supported by a recent study where we demonstrated that patients escorted by HEMS had an increased severity score and more often had a critical care intervention performed compared with the assisted patients. 3 …”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent study where we demonstrated that patients escorted by HEMS had an increased severity score and more often had a critical care intervention performed compared with the assisted patients. 3 Although the mortality at day 30 and day 365 among the assisted patients were lower compared with the airlifted patients, it was a surprise that the mortality at day 1 did not differ significantly between the two groups. The reason for this is unknown and needs to be further explored, but it should be noted that not all emergency conditions require air transportation to a university hospital even though they may be critically unwell, and hence, the patients might be correctly triaged to a DGH.…”
Section: Other Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…We previously found 5 that approximately two-thirds of patients attended to by physician-paramedic–staffed Danish HEMS have severe illness or injury and that the diagnostic groups most commonly seen consist of patients with time-critical conditions, such as cardiovascular emergencies, neurovascular emergencies, and severe trauma. Furthermore, we found 5 that 14% of HEMS dispatches are rejected mainly owing to weather conditions below minimal HEMS operating requirements. Consequently, a group of patients triaged by the emergency medical dispatch centers (EMDCs) to be in need of HEMS was left to be attended solely by ground EMS (GEMS) units.…”
Section: Introductionmentioning
confidence: 99%